STUDI KRITIK MATAN HADIS: - Siti Rohmaturrosyidah Ratnawati; Ali Yasmanto (Al-Bukhari : Jurnal Ilmu Hadis, 2019)
To determine whether a hadith is ????? or not is not enough if the research is carried out only to focus on aspects of its sanad, but research on content (al-matn) of ?ad?th is also a step that should not be abandoned, because there is no guarantee that if sanad of a ?ad?th is ????? (????? al-isn?d), so the matn of ?ad?th is ????? (????? al-matn) too. However, the studies of critics on matn al- ?ad?th have so far still tend to be few. For that reason, through this paper, the authors tried to examine about the critique of matn al- ?ad?th as an attempt to test the validity of the ?ad?th of Rasulullah Saw. from the side of its content (al-matn). A Hadith is declared as ????? al-matn if it fulfills two criteria, which is avoiding sy?dz and free from ?illat. The steps that can be taken to critique the content of ?ad?th are: compiling ?ad?th that are intertwined in the same theme, conducting research on content of ?ad?th with ????? ?ad?th approach and approach of the Qur'an, conducting research on content of ?ad?th with language approach, and research content of ?ad?th with a historical approach.